ChaSAM: An Architecture Based on Perceptual Hashing for Image Detection in Computer Forensics - Santos, Hericson Dos; Martins, Tiago Dos Santos; Barreto, Jorge Andre Domingues; Nakamura, Luis Hideo Vasconcelos; Ranieri, Caetano Mazzoni [UNESP]; De Grande, Robson E.; Filho, Geraldo P. Rocha; Meneguette, Rodolfo I. (Institute of Electrical and Electronics Engineers (IEEE), 2024)
The growing prevalence of digital crimes, especially those involving Child Sexual Abuse Material (CSAM) and revenge pornography, highlights the need for advanced forensic techniques to identify and analyze illicit content. While cryptographic hashing is commonly used in computer forensics, its effectiveness is often challenged because criminals can modify original information to create a new cryptographic hash. Perceptual hashes address this problem by focusing on the visual identity of the file rather than its bit-by-bit representation. This study introduces ChaSAM Forensics, a methodology that efficiently identifies illicit material using perceptual hashing techniques to track and identify illicit content, with a focus on child abuse material. Two new perceptual hashing algorithms, chHash and domiHash, were designed for integration into ChaSAM. The results showed that, under the tested conditions, the proposed chHash algorithm was more accurate than the established pHash algorithm when applied in a single iteration. Combinations of algorithms in two iterations were also assessed.
Keywords: Forensic computing; image detection; perceptual hashing; similarity